INOVASI PRODUKSI MINYAK KAYU MANIS DENGAN MENGGUNAKAN TEKNIK HIDRODISTILASI VAKUM - Andita Rusliawan; Dina Mukti Wijayanti; Bambang Pramudono (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Cinnamon oil is processed from cinnamon bark that has a high selling price. Cinnamon oil can be produced through a process either distillation or extraction. In this study, cinnamon bark is washed, dried, milled, and sieved to obtain size 2-3; 0.85-2; <0.85 mm. Then vacuum hydrodistillation is carried out with 800mL of water, 100 grams of cinnamon bark, at 70 ° C and 450mmHg (0.59 atm). Product from vacuum hydrodistillation is then measured and analyzed for levels cinnamic aldehyde. Optimum variables in this study are 0.85-2mm particle size and 4.5 hours which give the greatest yield is 3.02 (g oil produced/100 g cinnamon bark). Product of cinnamon oil with vacuum hydrodistillation have a good quality with  72.60% cinnamic aldehyde and fulfilling the standards of cinnamon oil.